2012
DOI: 10.1075/bct.45.03gar
|View full text |Cite
|
Sign up to set email alerts
|

Can iterated learning explain the emergence of graphical symbols?

Abstract: This paper contrasts two influential theoretical accounts of language change and evolution – Iterated Learning and Social Coordination. The contrast is based on an experiment that compares drawings produced with Garrod et al.’s (2007) ‘pictionary’ task with those produced in an Iterated Learning version of the same task. The main finding is that Iterated Learning does not lead to the systematic simplification and increased symbolicity of graphical signs produced in the standard interactive version of the task.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 0 publications
7
53
0
Order By: Relevance
“…Full conventionalization of a single order might require a larger time scale with more trials, and perhaps additional concomitant factors. For instance, the frequent change of task-partners within a 'speech community' can radically enhance the conventionalization effect as indicated in previous semiotic experiments (Garrod & Doherty, 1994;Garrod, Fay, Rogers, Walker, & Swoboda, 2010) and agent-based simulations (Baronchelli & Diaz-Guilera, 2012;Baronchelli, Gong, Puglisi, & Loreto, 2010;Loreto & Steels, 2007;Puglisi, Baronchelli, & Loreto, 2008;Steels, 2011).…”
Section: Discussionmentioning
confidence: 91%
“…Full conventionalization of a single order might require a larger time scale with more trials, and perhaps additional concomitant factors. For instance, the frequent change of task-partners within a 'speech community' can radically enhance the conventionalization effect as indicated in previous semiotic experiments (Garrod & Doherty, 1994;Garrod, Fay, Rogers, Walker, & Swoboda, 2010) and agent-based simulations (Baronchelli & Diaz-Guilera, 2012;Baronchelli, Gong, Puglisi, & Loreto, 2010;Loreto & Steels, 2007;Puglisi, Baronchelli, & Loreto, 2008;Steels, 2011).…”
Section: Discussionmentioning
confidence: 91%
“…This indicates that high amounts of iconic structure (postulated for earlier stages of language) may have blocked the use of combinatorial structure in the early evolution of language. Other work in the social coordination paradigm has investigated how conventionalization through repeated use can simplify signals (Garrod, Fay, Rogers, Walker, & Swoboda, 2010).…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Mesoudi and Whiten, 2008;ScottPhillips and Kirby, 2010). Garrod (2010), for instance, found that by contrasting two transmission dynamics -vertical cultural transmission and repeated pairwise interaction -chains of learners would produce different outputs. Specifically, the graphical communication systems that emerged were better suited to their specific forms of transmission: forms transmitted vertically tended to retain their iconic appearance, whereas the interactively produced forms decreased in complexity through taking on a more symbolic aspect.…”
Section: Combining Approach Esmentioning
confidence: 99%